An Overview of Omnibus Law from Point of Establishing Legal System in Indonesia - Faisal Afda'u; Siti Ummu Adillah; Latifah Hanim (Law Development Journal, 2022)
The purpose of this research to get a clear answer study review of omnibus law from the point of view of the formation of the legal system of legislation in Indonesia and the research approach method used is normative juridical by reviewing legal principles and analyzing existing laws and regulations and reviewing the formation of laws and regulations namely Act No. 12 of 2011 amended by Act No. 15 of 2019 with the omnibus law. Based on the research it can be concluded that the establishment of omnibus law if viewed from the perspective of the formation of legislation, the position of the omnibus law in the hierarchy is the same as the law regulated in Article 7 paragraph 1 of Act No. 12 of 2011 concerning the formation of legislation. In theory, the position of omnibus law has not been regulated, but rational legitimacy can be found in the system of forming legislation in Indonesia. The position of omnibus law can be based on Act No. 12 of 2011 which has been amended by Act No. 15 of 2019 concerning the system for the formation of legislation and the process of forming legislation on academic texts and the draft omnibus law draft is in accordance with the formation of legislation, namely Act No. 12 of 2011 was amended by Act No. 15 of 2019. This law is a substantive requirement and a technical requirement in the formation of laws and regulations in Indonesia. The consequence of implementing the omnibus law is that the existing law is still valid, except for some articles (legal material) that have been replaced or declared invalid and the existing law is no longer enforced.